2019
DOI: 10.1097/mph.0000000000001431
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic Fungal Infections in Children With Leukemia—Risk Factors and Outcome: A Multicentric Study

Abstract: Background: Invasive fungal infections, including hepatosplenic fungal infections (HSFI), cause significant morbidity and mortality in children with leukemia. There are not enough data to support for the best approach to diagnosis of HSFI in children, nor for the best treatment. Procedure: In this multicentric study, we assessed the demographic data, clinical and radiologic features, treatment, and outcome of 40 children with leukemia and HSFI from 12 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…were isolated from blood cultures in 30% of those cases. Celkan et al [ 29 ], in a multicentric study from Turkey, recently reported that 8 out of 40 (22.5%) children with HSC had Candida spp. and only one case was C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…were isolated from blood cultures in 30% of those cases. Celkan et al [ 29 ], in a multicentric study from Turkey, recently reported that 8 out of 40 (22.5%) children with HSC had Candida spp. and only one case was C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the incidence of invasive fungal infection is reported to be 9%‐10% with mortality rates ranging from 21% to 48% . However, HSFI is rare in children with leukaemia, and the incidence of HSFI is not known. Risk factors for invasive candidiasis in patients with haematological malignancies include neutropenia, corticosteroid therapy, mucositis and the presence of central venous catheters …”
Section: Introductionmentioning
confidence: 99%
“…CNSFI was most commonly accompanied by lung involvement, followed by paranasal IFI in our patients. In our recently published study, in 40 children with leukemia and hepatosplenic fungal infection, 57% were accompanied by fungal infection in other regions, most commonly the lungs 31…”
Section: Discussionmentioning
confidence: 89%